Comportamento alimentar e sedentarismo: uma aplicação prática do método científico no ensino médio - Lima, Laíse América de Almeida (2022)
Meaningful learning is that which goes beyond mnemonic practices and takes place in a consistent and relevant way in the subject's life. One of the ways to develop knowledge is through active methodologies that can be represented by scientific investigation, where there is a systematic search for the student's protagonism, grounding their knowledge through their discoveries. This work presents the structuring and application of a didactic sequence for the discussion of healthy habits, highlighting them as one of the necessary conditions to achieve a satisfactory quality of life and also proposes the structuring of a manual that will guide the biology teacher in the execution of the plan and that may be adapted for other content. The contents covered were: food, nutrition, general aspects of a healthy life; digestive systems, locomotor and chronic non-communicable diseases (NCDs), aiming to implement with the school community, a work to analyze the importance of a balanced diet and the practice of physical activity. The basic contribution of the research was qualitative. As for the method used, it is what we call action research. The activities took place remotely, since we had been working in the modality of remote emergency education, since March 18, 2020 due to the social isolation imposed by the COVID-19 pandemic. The work with the students started through informal conversation and survey, followed by a pre-test. At first, it was observed that they had prior knowledge regarding healthy living habits and a balanced diet, but such knowledge needed guidance so that the understanding could be expanded. The pre-test indicated a deficiency in terms of understanding how the body uses energy from food. Another aspect observed refers to the lack of immediate identification of which foods were building, energetic and those rich in fiber. In addition to the fact that many students are unaware of the composition of the digestive system and its physiology. Finally, the initial data collected still detected some doubts about the structure and classification of muscles, the relationship between sedentary lifestyle and CNCDs. After the development of the activities proposed by the didactic sequences developed, it was verified in the post-test significant changes in the obtained results, demonstrating that the developed work was successful in the teaching-learning process. We found that there was a considerable increase in the understanding of metabolism, and it is possible to see that they began to understand a little better the function of the component structures of the digestive system and their respective functions, as well as they began to understand the dynamics of the muscular system, in addition to relating to more significantly the issue of a sedentary life with obesity and related diseases. It should be noted that the proposal presented here is intended to enable a better performance of students in classes by introducing activities that encourage them to express what they think about the topic discussed and that they change from mere spectators to questioners of the surrounding environment, in addition to seeing biology and its themes, not with something distant, but that it has direct meaning in our everyday actions.